A Survey on Microgrid Control Techniques in Islanded Mode. (15th October 2020) - Ekanayake, Uthpala N.; Navaratne, Uditha S.
Abstract : Traditional power networks with generation in upstream and consumption in the downstream were controlled with centralized controls like SCADA. However, in order to facilitate the penetration of distributed generation, the concept of microgrid was popularized. A microgrid can operate both in grid-connected and in islanded modes. One of the challenges in the microgrid environment is to provide both voltage control and maintain the system frequency while ensuring the stability of the network. This paper is a literature survey focused on different microgrid control techniques with different levels of communication especially in islanded operation.